CLINICAL AND MORPHOLOGICAL CHARACTERISTICS OF THE HUMAN PLACENTA AND ITS ULTRASOUND PARAMETERS IN NORMAL PREGNANCY - Mamatkobilova , Sohiba (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
The placenta is the fundamental organ of pregnancy, serving as the interface between the maternal and fetal circulatory systems. It provides respiratory, nutritional, endocrine, and immunological functions, ensuring optimal fetal development. Disturbances of its formation and maturation are closely associated with obstetric complications such as preeclampsia, intrauterine growth restriction (IUGR), placental insufficiency, and preterm labor. Recent literature highlights the clinical significance of both morphological and ultrasound (US) parameters of the placenta. Placental thickness (PT) has been widely investigated as a non-invasive marker reflecting gestational age, placental function, and fetal well-being. Gbande et al. (2023) demonstrated that PT increases progressively across trimesters and strongly correlates with gestational age (r ≈ 0.87, p < 0.00001). Morphological studies describe normal placenta as a discoid organ, with villous structures, balanced vascularization, and stable dimensions by late pregnancy (Sagberg et al., 2024). Given the predictive value of these findings, systematic analysis of normal placental parameters is essential for early identification of pregnancy risks.